Fundamental Constants: Improving Our Knowledge on the 229mThorium Isomer: Toward a Test Bench for Time Variations of Fundamental Constants (Ann. Phys. 5/2019). Issue 5 (9th May 2019) - Thirolf, Peter G.; Seiferle, Benedict; von der Wense, Lars
Abstract : In article number1800381, Peter G. Thirolf and co‐workers discuss the introduction of the low‐energy, isomeric first excited state of 229 Th as a candidate for an ultra‐precise nuclear frequency standard. Various applications for such a 'nuclear clock' are given, from improved accuracy of satellite‐based navigation to chronometric geodesy, dark matter search or an enhanced sensitivity for temporal variations of fundamental constants. Recent achievements towards exploiting 229m Th as test bench for fundamental physics are reviewed.